Can neutrophil/lymphocyte ratio be a novel biomarker of inflammation in children with asthma?. (August 2016) - Nacaroglu, Hikmet Tekin; İsgüder, Rana and Bent, Sultan and Erdem Bahceci, Semiha and Ceylan, Gökhan and Korkmaz, Hüseyin Anıl and Karaman, Sait and Unsal Karkıner, Canan Sule and Can, Demet
Neutrophils are known to play a role in airway inflammation and are activated in inflammatory lung diseases such as asthma. In adult studies the neutrophil/lymphocyte ratio (NLR) was found to be a possible biomarker for both airway and systemic inflammation. However, there is a limited understanding regarding NLR in the pediatric age group. To assess NLR as a biomarker for inflammation in pediatric asthma, 54 children admitted to hospital with exacerbation of asthma between March and October 2013 were enrolled into our study. Complete blood counts were obtained during both exacerbation and an asymptomatic period covering at least 3 months after exacerbation. NLRs of the study group during both exacerbation and the asymptomatic period were compared and these two datasets were then compared with the control group. The study group comprised 27 boys (50%) and 27 girls (50%) with a mean age of 120 ± 36 months. Of the total number of patients, 3.7% had mild, 94.4% had moderate, and 1.9% had severe exacerbation of asthma. The NLRs of the study group were found to be significantly higher during exacerbation compared with both the asymptomatic period and the control group ( P = 0.017, P = 0.003). Our study suggests that NLR may be effective and usable measurable biomarker for determining inflammation in cases of pediatric asthma during acute exacerbation period. However, a broad analysis of dependent and independent variables in further prospective studies, is still required. Trial registration: Not applicable.